Invasion of the bucco-mandibular space by oral squamous cell carcinoma: histopathological analysis of invasion pattern - Kugimoto, Takuma; Nishii, Naoto; Oikawa, Yu; Kuroshima, Takeshi; Hirai, Hideaki; Tomioka, Hirofumi; Michi, Yasuyuki; Kayamori, Kou; Sakamoto, Junichiro; Iwanaga, Joe; Tubbs, R. Shane; Ikeda, Tohru; et al. (Frontiers in Oncology, 2023)
Background: This study aimed to determine the patterns of invasion of oral squamous cell carcinoma (OSCC) into the bucco-mandibular space (BMS) using detailed histopathological analysis and to assess clinical outcomes. Methods: Patients with OSCC who underwent segmental mandibulectomy or hemi-mandibulectomy combined with resection of the BMS between 2012 and 2021 were included. The invasions of the BMS were classified into three patterns. Pattern A was defined as a horizontal invasion, Pattern B as a vertical invasion, and Pattern C as an expansive invasion. Results: In total, 109 patients were reviewed. Of these 109 patients, the primary tumor affected the lower gingiva in 78 patients, the buccal mucosa in 18 patients, and was a primary intraosseous carcinoma of the mandible in 13 patients. Invasion of the BMS was significantly associated with a higher pathological T stage, positive/close margins, and lower disease-free survival (DFS) rates. The DFS rates were 86.7% and 66.0% in the BMS non-invasion and invasion groups, respectively. The DFS rates for each type of invasion were 82.1% for Pattern A, 67.4% for Pattern B, and 48.0% for Pattern C (P=0.277). Conclusion: Patients with BMS invasion have a poorer prognosis than those without invasion of the BMS. Therefore, adjuvant therapy is necessary, especially in Patterns B and C. Evaluation of preoperative BMS invasion patterns is important for predicting the prognosis of OSCC.